SPEAKING TO BELONG: HOW LANGUAGE USE REFLECTS IDENTITY IN THIRD CULTURE AND LONG-TERM IMMIGRANT ADOLESCENTS - Ghazali, Diandra Nayyara Putri Disya; Sudarwati, Emy (Faculty of Administrative Science, Universitas Brawijaya, 2025)
This study aims to explore the influence of language use on identity and belonging in a Third Culture Kid (TCK) and a long-term immigrant adolescent. Although numerous research investigates language and identity independently, few directly compare these two domains. This research aims to investigate how adolescents from multicultural backgrounds utilize language in familial, social, and educational settings, and how these linguistic patterns affect their sense of belonging. Data were acquired using semi-structured interviews and processed using thematic analysis within a qualitative framework. Research indicates that Indonesian functions as the emotional and intimate language among families, whereas English is preferred in peer interactions, schooling, and everyday activities. Cultural ties are mostly sustained through cuisine, behaviors, and deliberate language selection. The TCK portrays feelings more authentically in Indonesian and cultivates a hybrid identity, while the long-term immigrant utilizes English for emotional expression and experiences a deeper connection to the host culture due to linguistic predominance. In conclusion, language serves a dynamic and context dependent function in influencing how adolescents navigate their identities across cultures.